EFEKTIVITAS PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PEMAHAMAN IBU TENTANG STUNTING PADA BALITA - Ariyana, Ariyana (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Stunting is a serious public health problem in Indonesia, especially in toddlers, and is strongly influenced by mothers' knowledge and behaviour in child care. This study aims to determine the effectiveness of health education on increasing mothers' understanding of stunting in toddlers. This study used a pre-experimental design with a one group pretest-posttest approach. The study sample totalled 80 mothers who had toddlers and were selected through purposive sampling technique. The purpose of the study was to provide interventions in the form of health education with lecture methods and interactive discussions using visual media in increasing mothers' understanding of stunting. the research site was conducted in Sidrap district. The instrument used was a structured questionnaire that was tested during the pre-test and post-test. Data analysis was conducted through descriptive tests (mean, median, mode, and standard deviation), normality test (Shapiro-Wilk), paired t-test, and large effect test (Cohen's d). The results showed that there was a significant increase in maternal understanding scores after being given health education, with a pre-test mean value of 62.40 increasing to 84.75 in the post-test (p < 0.05). The large effect test showed a Cohen's d value of 3.05 which indicated that the intervention had a very large effect. It can be concluded that health education is significantly effective in improving mothers' understanding of stunting in toddlers. These results indicate the importance of educative interventions as a stunting prevention strategy that can be integrated into maternal and child health service programmes at the community level.